2020
DOI: 10.1016/j.nicl.2020.102416
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible metabolic topographies associated with multiple system atrophy: Network and regional analyses in Chinese and American patient cohorts

Abstract: Highlights This study produced reliable metabolic brain networks for multiple system atrophy. Network scores discriminated this disorder from other major forms of Parkinsonism. Network scores correlated with clinical stages and motor symptoms in this disorder. The network was highly reproducible across Chinese and American patient cohorts. Network scores provided a clinically useful biomarker in a multi-center setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Compared with 15 healthy controls, metabolic characteristics of MSA patients, MSA-D, MSA-MCI, and MSA-NC were all in accordance with MSA-related pattern (MSARP) observed by previous study ( 34 , 35 ) ( Supplementary Figure 2 ).…”
Section: Resultssupporting
confidence: 87%
“…Compared with 15 healthy controls, metabolic characteristics of MSA patients, MSA-D, MSA-MCI, and MSA-NC were all in accordance with MSA-related pattern (MSARP) observed by previous study ( 34 , 35 ) ( Supplementary Figure 2 ).…”
Section: Resultssupporting
confidence: 87%
“…This pattern was also observed in Chinese and American patient cohorts where the metabolic topography of MSA‐P includes hypermetabolism in the superior frontal gyrus. 24 However, considering that iRBD patients rarely develop MSA instead of PD or DLB, 10 the impact of metabolic patterns associated with MSA needs to be further investigated in large sample data. Interestingly, metabolic decrease in the right premotor cortex correlated with decline in the TMT‐B performance in iRBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The last decade has witnessed the development and clinical validation of large-scale metabolic brain networks involving widely-distributed functional neuroanatomical structures. This was especially true with FDG PET in patients with PD and atypical PD such as multiple system atrophy, progressive supranuclear palsy and cortico-basal degeneration (Teune et al, 2013 , Niethammer et al, 2014 , Peng et al, 2014b , Ge et al, 2018 , Schindlbeck and Eidelberg, 2018 , Meles et al, 2020 , Shen et al, 2020 ). Novel classification algorithms based on the expression levels of these networks provided accurate differential diagnosis even in early-stage parkinsonian populations (Tang et al, 2010 , Tripathi et al, 2016 ), given that DBS was ineffective in pathologically-confirmed patients with atypical PD who were inadvertently misdiagnosed to receive the invasive treatment (Meissner et al, 2016 ).…”
Section: Development Of New Frontiersmentioning
confidence: 99%